(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
A study was conducted to examine the culture and growth performance of Spirulina platensis in three different concentrations (25, 50 and 75 percent) of digested rotten orange (DRO) and Kosaric medium (KM) as control for three months. Each experiment was done in triplicates under fluorescent light in light: dark (12 hour: 12 hour) condition for a period of 14 days. Cell weight, chlorophyll a content of Spirulina platensis and physico-chemical parameters of cultured media (temperature, pH, light intensity) were measured at every alternative day. During the culture period, temperature was more or less similar and ranged from 30.1 to 31.4˚C. The range of light intensities was recorded from 2660 to 2770 lux/ /s during the culture period. The maximum pH was recorded 9.9 in 25% digest rotten orange (DRO) on 8th day of the culture and minimum was recorded 8.2 in all the medias on the initial day of the culture. The growth rate of Spirulina platensis cultured in supernatant of DRO and KM were varied. The initial cell weight of Spirulina platensis was 0.0023 mg/L that attained maximum cell weight of 12.44 mg/L in Kosaric medium on the 10th day of culture. Besides that, the maximum cell weight was 7.679, 12.366, and 9.455 mg/L when cultured in supernatant of 25, 50, and 75% in DRO on the 10th day of the culture. While, the initial chlorophyll a content of Spirulina platensis was 0.0015 mg/L which attained the highest content of 10.54 mg/L when grown in KM. The highest chlorophyll a content of Spirulina platensis was 6.926 mg/L when grown in 25% DRO, it was 10.476 mg/L when grown in 50% DRO, and it was 9.140 mg/L when grown in 75% DRO on the 10th day of the culture. This study showed that, the growth performance of Spirulina platensis was higher in supernatant of 50% DRO than 25 and 75% DRO. This concentration of medium gave satisfactory results compared with standard KM. This variation probably occurred because of differences in nutrient concentrations and composition of the medium. Therefore, it can be concluded that, the concentration of 50% DRO is suitable and favorable for Spirulina platensis culture. Asian Australas. J. Biosci. Biotechnol. 2018, 3 (3), 208-224